The Influence of Digital Literacy and Learning Styles on Students' Mathematics Learning Outcomes - Hasibuan, Nabila Sari; Lubis, Mara Samin (Unnes Journal of Mathematics Education, 2024)
The aim of this research is to determine whether or not there is an influence of digital literacy on students' mathematics learning outcomes, whether or not there is an influence of learning styles on students' mathematics learning outcomes, and whether or not there is an influence of digital literacy and learning styles on students' mathematics learning outcomes. This research is quantitative research with an ex post facto type. This research was conducted at MTsN 3 Medan. Data collection methods use questionnaires and documentation. The analysis techniques used are descriptive analysis, data analysis prerequisite tests, and hypothesis testing. The research results show that there is an influence of digital literacy on students' mathematics learning outcomes, as evidenced by (Sig.) 0.005 ˂ 0.05. There is an influence of learning style on students' mathematics learning outcomes, as evidenced by (Sig.) 0.005 ˂ 0.05. There is a significant influence between digital literacy and learning style on mathematics learning outcomes, with a Sig value of < 0.05. This is proven by the results of multiple regression analysis with a Sig value of digital literacy of 0.037 and a Sig value of learning style of 0.035 ˂ 0.05. Digital literacy and learning styles contribute to student mathematics learning outcomes by 42.5%.